Implication of anti-angiogenic VEGF-A165b in angiogenesis and systolic function after reperfused myocardial infarction. (25th November 2020) - Marcos Garces, V; Rios-Navarro, C; Hueso, L; Diaz, A; Bonanad, C; Ruiz-Sauri, A; Sanz, M.J; Chorro, F.J; Piqueras, L; Bodi, V
Abstract: Background: Angiogenesis participates in re-establishing microcirculation after myocardial infarction (MI). Purpose: In this study, we aim to further understand the role of the anti-angiogenic isoform vascular endothelial growth factor (VEGF)-A165b after MI and explore its potential as a co-adjuvant therapy to coronary reperfusion. Methods: Two mice MI models were formed: 1) permanent coronary ligation (non-reperfused MI), 2) transient 45-min coronary occlusion followed by reperfusion (reperfused MI); in both models, animals underwent echocardiography before euthanasia at day 21 after MI induction. Serum and myocardial VEGF-A165b levels were determined. In both experimental MI models, functional and structural implication of VEGF-A165b blockade was assessed. In a cohort of 104 ST-segment elevation MI patients, circulating VEGF-A165b levels were correlated with cardiovascular magnetic resonance-derived left ventricular ejection fraction at 6-months and with the occurrence of adverse events (death, heart failure and/or re-infarction). Results: In both models, circulating and myocardial VEGF-A165b presence was increased 21 days after MI induction. Serum VEGF-A165b levels inversely correlated with systolic function evaluated by echocardiography. VEGF-A165b blockage increased capillary density, reduced infarct size, and enhanced left ventricular function in reperfused, but not in non-reperfused MI experiments. In patients, higher VEGF-A165b levels correlated with depressed ejection fraction and worse outcomes. Conclusions: In experimental and clinical studies, higher serum VEGF-A165b levels associates with a worse systolic function. Its blockage enhances neoangiogenesis, reduces infarct size, and increases ejection fraction in reperfused, but not in non-reperfused MI experiments. Therefore, VEGF-A165b neutralization represents a potential co-adjuvant therapy to coronary reperfusion. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This study was funded by "Instituto de Salud Carlos III" and "Fondos Europeos de Desarrollo Regional FEDER" (Exp. PIE15/00013, PI17/01836, PI18/00209 and CIBERCV16/11/00486).